Sensitivity analysis of a pathway with respect to fast and small temperature change. (July 2019) - Zakhartsev, Maksim; Ruoff, Peter
Abstract: Temperature affects all enzymes simultaneously in a metabolic system. The enzyme concentration in a biochemical system can be considered as invariant under fast and small temperature change. Therefore, the total sensitivity of a steady state flux through a pathway with respect to the temperature can be expressed as: the apparent activation energy of a steady state pathway flux equals the sum of weighted activation energies of the individual reactions contributing to the flux, where the weighting factors are the flux control coefficients of these reactions in the context of the network. Correspondingly, since the elasticity of any enzyme with respect to temperature is always nonzero, only the reactions with a nonzero flux control coefficient contribute accordingly to the temperature sensitivity of the pathway. Highlights: Activation energy (Ea) of a pathway flux is the sum of Ea's of the individual reactions weighted by the flux control coefficients of these reactions. The activation energy (Ea) of flux through a pathway is decomposed to elemental components. The pathway Ea is the sum of Ea's of the individual reactions weighted by the flux control coefficients of these reactions.